Full frontal feminism a young women's guide to why feminism matters - Valenti, Jessica (Seal Press, 2014)
You're a hardcore feminist I swear -- Feminists do it better (and other sex tips) -- Pop culture gone wild -- If these uterine walls could talk -- Guys gone wild, girls gone mild -- Material world -- My big fat unnecessary wedding -- I promise I won't say "herstory" -- Boys do cry -- Beauty cult -- Sex and the city voters, my ass -- Get to it -- Resources -- Notes